Orientation of larval and juvenile horseshoe crabs Limulus polyphemus to visual cues: Effects of chemical odors - Julie M. MEDINA, Richard A. TANKERSLEY (Current Zoology, 2010)
Adult horseshoe crabs Limulus polyphemus have long served as models for the study of vision in marine arthropods. Yet, little is known about the ability of early life history stages to detect and respond to visual cues. We examined the visually directed movements of larvae and first stage juveniles to horizons containing dark visual targets of different sizes. The study tested the hypotheses that (1) larval and juvenile crabs can detect and respond to visual targets and (2) the direction of orientation varies with the presence of chemical cues associated with settlement habitats. Orientation of larval and juvenile crabs to rectangles subtending angles from 30-330o was tested in a circular arena containing water that either lacked estuarine chemical cues (offshore water) or contained odors from aquatic vegetation or known predators. In the absence of chemical odors, larvae oriented toward and juveniles moved away from dark horizons subtending angles > 60°. When placed in water containing chemical odors from potential nursery habitats, including the seagrasses Halodule wrightii and Syringodium filiforme, crabs reversed their direction of orientation relative to their responses in offshore water. Odors from two known predators, the mummichug Fundulus grandis and blue crab Callinectes sapidus, had no affect on the orientation of larvae. Yet, juveniles responded to both odors by moving toward the visual target. Results support the hypothesis that the visual orientation of larval and juvenile horseshoe crabs changes upon exposure to habitat and predator cues and that the direction of the response undergoes an ontogenetic shift following metamorphosis [Current Zoology 56 (5): 618–633, 2010].